Role model for non-native speakers’ English pronunciation: ‘an investigation into the attitude of adult learners in Bangladesh’ - Mahjabin, Mohona (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.